2022
DOI: 10.2147/ppa.s348790
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Mobile Health in Developing Countries During COVID-19: Vietnamese’s Perspectives from Different Age Groups and Health Conditions

Abstract: Background: Vietnam's economy and intellectual standards have witnessed significant development, improving conditions for residents to acquire novel mHealth applications. Additionally, the outbreak of the COVID-19 pandemic has influenced Vietnamese awareness of healthcare; however, previous studies have only been clinician-centered rather than customer-centered. Methods: This study addresses this literature gap by interviewing 50 Vietnamese participants grouped by age, namely Generation X, Generation Y, and Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Similarly, Guo et al (2016) found that the effects of personalisation on trust and behavioural intentions are stronger for younger people compared to older people. The existing literature focusing on Gen-Z in the context of m-health is scarce and Mobile health application usage most similar studies focus on digital interventions and e-health initiatives rather than m-health apps (Aydin and Kumru, 2022;Curtis et al, 2019;Nguyen et al, 2022). However, the characteristics of this generation such as being digitally native and having been born in an era where internet-enabled mobile devices are easily accessible, make them prospective users of m-health services (Coughlin et al, 2007).…”
Section: Generation Z and Mobile Healthmentioning
confidence: 99%
“…Similarly, Guo et al (2016) found that the effects of personalisation on trust and behavioural intentions are stronger for younger people compared to older people. The existing literature focusing on Gen-Z in the context of m-health is scarce and Mobile health application usage most similar studies focus on digital interventions and e-health initiatives rather than m-health apps (Aydin and Kumru, 2022;Curtis et al, 2019;Nguyen et al, 2022). However, the characteristics of this generation such as being digitally native and having been born in an era where internet-enabled mobile devices are easily accessible, make them prospective users of m-health services (Coughlin et al, 2007).…”
Section: Generation Z and Mobile Healthmentioning
confidence: 99%
“…The self-risk assessment function needs the information before classifying the user’s risk level. Previous studies have shown that privacy and confidentiality are barriers to using mHealth in older adults [ 32 ]; hence, older adults may be concerned about the privacy and confidentiality of their information and they did not continue to complete the form and get the result.…”
Section: Discussionmentioning
confidence: 99%
“…[14], [15], [23], [27], [28], [32], [36], [39], [43], [45], [47], [49], [51], [55], [57], [60], [61], [65], [71], [72], [75], [81], [83], [90], [97], [101], [102], [108], [116], [119], [124], [138], [139] These articles take into account the quality attributes of functionality and reliability since a software must fulfill the functions for which it was created, but also that software must remain operational over time, these requirements are perfectly aligned to address the problems that Covid-19 is presenting.…”
Section: Quality Attributes Artíclesmentioning
confidence: 99%